EFFECT OF TAX INCENTIVES ON MSMEs’ TAX COMPLIANCE IN NIGERIA (Journal of Business Management and Accounting, 2024)
Tax incentives have been used as tools to encourage investments and tax compliance from businesses. Little is known about the effect of tax incentives on tax compliance of Micro, Small and Medium Enterprises (MSMEs) in Nigeria.  The study, therefore, investigated the effect these tax incentives (the Nigerian government tax exemption to MSMEs with income of a particular threshold and low-interest financing) have on the tax compliance of MSMEs in Nigeria. The study adopted quantitative research and administered questionnaires to MSMEs in Nigeria. Guided by the theories of social influence and slippery slope, the study employed the regression technique for the analysis and concluded that tax incentives have a significant effect on the tax compliance of MSMEs in Nigeria. Also, tax exemption and low-interest financing have a significant effect on the tax compliance of MSMEs in Nigeria. The study has contributed to the body of knowledge by showing the effect the government tax policy of tax exemption to MSMEs has on tax compliance. The different incentives of government are not sufficiently communicated to these businesses to take advantage of. It is, therefore, recommended that government policies especially on incentives to MSMEs should be well broadcast through different social media platforms for them to benefit.